Production, characterization and assessment of reformulated bio-mixture fuel from a mixture of various raw feedstock's and the effect of n-butanol as an additive on bio-mixture blends. (November 2021) - Subhash, G.V.; Sivapirakasam, S.P.; Mohan, Sreejith; Harisivasri Phanindra, K.
Abstract: The current experimental study focuses on enhancing the characteristics and properties of bio-mix test fuel samples by using an additive such as n-butanol. Raw bio-mix fuel samples were prepared through a method of bio-mix to enhance the quality of biodiesel from the raw mixture of edible and non-edible feedstocks. In this experimental investigation, five test samples were prepared such as BSBW1, BSBW2, BSBW3, BSBW4 and BSBW5 at various blended ratios from the raw mixture of soapnut, borassus flabellifer, waste crude cotton seed oils and transesterified for the formation of bio-mix methyl ester fatty acids. From experimental results, it was observed that BSBW4 and BSBW5 recognized as optimum blends exhibited lower acid value than BSBW1, BSBW2 and BSBW3 blends. The fatty acid compositions of optimum bio-mixed samples were examined by using Gas Chromatography and Mass Spectrometry (GC-MS) to determine the characterization of tested fuels. 10% of the n-butanol additive deployed to the optimal blends BSBW4 and BSBW5 referred to as BSBW4B10 and BSBW5B10 were chosen for further experimental analysis. Experimental test results demonstrated that oxidation stability, cetane number, saturated fatty acid methyl ester, cold flow properties were improved while flash point, viscosity, iodine number, density, free fatty acid and heating value decreased. From this experimental investigation, it was concluded that the method of the n-butanol additive added to the bio-mix fuel samples could enhance the quality of the fuel and met the BIS, ASTM and EN testing procedures and standard limits as compared to all bio-mix and individual fuel samples respectively. Graphical abstract: Image 1 Highlights: Analysis of biodiesel properties by adding n-butanol additive to bio-mixture fuel. Novel study of the effect of n-butanol additive on bio-mixture fuel. Properties of n-butanol blended bio-mixture fuel were compared with bio-mixture fuel without additive. Biomixture shows higher saturation methyl ester and oxidation stability. n-Butanol addition in bio-mixture fuel reduces density, kinematic viscosity and flash point.